(untitled) (Research, Society and Development, 2022)
Introduction: During the first years of life, food plays a key role in the development and formation of eating habits that will be carried for life, habits that may come with benefits or harms to health, especially the importance of exclusive breastfeeding in the first six months of life. Methodology: A literature review was carried out, addressing as main topics the introduction of food and the Baby-Led Weaning (BLW) method. General Objective: To demystify and present the BLW method as an alternative of food introduction in early childhood, as well as its positive and/or negative points for the formation of feeding habits. Results and Discussion: There are several interconnected aspects that can influence positively or negatively during the infant’s introduction to food, which will directly impact the eating habits that will be acquired. These acquired eating habits have repercussions until adulthood and have implications on health status. Conclusion: In addition to presenting the benefits and harms during the introduction of food at the ideal time, monitoring with a professional nutritionist proved to be important when using the BLW method, providing support for a better development of the infant in order to avoid future health problems.